Allogenic Hematopoietic Stem Cell Transplantation from Related Donors in Fanconi Anemia - Amir Ali Hamidieh; Ardeshir Ghavamzadeh; Mohammad Jahani (International Journal of Hematology-Oncology and Stem Cell Research, 2009)
"n "n "n "n "n "n "n "n "n "n "n "n "nIntroduction: "n "nAllogeneic hematopoietic cell transplantation (HSCT) is the only therapeutic modality capable of "ncorrecting the hematologic manifestations of Fanconi Anemia (FA). "nThe development of well tolerated, immunosuppressive conditioning regimens for FA patients undergoing "nHSCT has proven to be a rather challenging task for hematologists. "nMethods: "n "nWe analyzed the outcome of 30 FA patients (median age at HSCT was 9 years age range, 2-32 years) "nwho underwent HSCT between 1992 and 2008 in Shariati Hospital Tehran, Iran. . Patients were transplanted "nfrom either an HLA-identical sibling or matched relative (n=29), or an HLA-partially matched relative(n=1). "nFour different conditioning regimens without radiation were used .Graft versus host disease (GVHD) "nprevention consisted of cyclosporine with methotrexate or cyclosporine alone. "nResults: "n "nThe median follow-up duration for survivors was 2.7 years (ranged 1 month to 12 years). The median "nsurvival time was 8.5 months. The 5-year overall survival was 43.6% (SE=10.0%). All surviving patients had "nnormal blood counts with full donor engraftment. "nThe median survival rate for patients who did or did not receive fludarabine in preparation for the allograft was "nnot statistically significant (p-value=1.0). "nConclusion: "n "nOur study demonstrates that none of the studied variables significantly affected the survival,